Private rental in later life: The growing site of housing precarity for older single women - Stone, Wendy; Reynolds, Margaret; Veeroja, Piret; Power, Emma; Perugia, Francesca; James, Amity (Council to Homeless Persons, 2024)
Housing insecurity among older people in Australia, risk of homelessness, and experiences of homelessness, continue to increase. In our recent research, Ageing in a Housing Crisis: Older People's Housing Insecurity and Homelessness in Australia, we enumerated increasing housing precarity and homelessness experienced by people aged 55 years and over, across the housing system. We drew on Australian Bureau of Statistics 2021 Census of Population and Housing data and the most recent Homelessness Estimates to conceptualise and enumerate the scale of the problem. Our research showed a tenure-wide housing precarity among older people, affecting homeowners with mortgages, renters - particularly older women - and people already experiencing homelessness.